Nekonvencionalne replike v slovenščini z anketno raziskavo med slovenskimi govorci - Meterc, Matej (Slavistična revija, 2020)
We define an unconventional reply as a fixed, unpredictable, inadequate, and usually humorous or absurd reply by person B to a statement by person A. The replies constitute a special type of phrasemes (subtype of phraseological replies) and are a special paremiological genre. Research conducted among 209 Slovene speakers is presented. We determine passive and active knowledge of twenty unconventional replies and the degree to which they are recognized as units belonging to a specific genre. We also present a list of other unconventional replies and variants.
Keywords: deautomatization; deavtomatizacija; frazeologija; frazeološka replika; humor; humour; paremiologija; paremiology; phraseological reply; phraseology; Slovene language; slovenščina